Aquí en Pahuatlán, el pez gordo se come al chico : migración en la Huasteca poblana - María Eugenia d’Aubeterre Buznego; María Leticia Rivermar Pérez (Les Cahiers ALHIM)
The illegal immigration of Mexicans in the 1980s from the Huasteca Region of Puebla to the U.S. represents a new phase of the historic cycle of migrations that started with the Bracero Migratrion Program in the decade of the 1940s.  Contrasting the latter with the ‘new’ migration in the municipality of Pahuatlán, Puebla, is one of the purposes of this paper.  We will document the change of lifestyle centered in production oriented to supply the regional and national demand, towards a different type of production, developed in the context of the expansion of global capitalism and the consolidation of a transnationalized market. The analysis is based on ethnographic work and in-depth interviews. The analysis deals with the perceptions and the meanings which participants attribute to practices and events lived from unequal positions in the scheme of relationships of social class, ethniticy and gender, which make them subjects, and at the same time they contribute to the shape of these schemes.